Investigation of Botulinum Neurotoxin Types from Clostridium botulinum Causing A Recent Outbreak in Vietnam - Huyen, La Thi Huong; Linh, Nguyen Thuy; Trung, Nguyen Thanh; Yen, Pham (VNU Journal of Science: Natural Sciences and Technology, 2021)
Clostridium botulinum is one of the causes of undiagnosed sudden deaths in humans due to the lethal botulinum neurotoxins (BoNTs). Foodborne botulism rarely occurs in developed countries because of being closely monitored, in opposite to developing countries including Vietnam. In the August 2020 food poisoning outbreak in Vietnam, presence of Clostridium botulinum and BoNTs was identified by culture and mouse bioassay, however, information regarding the possible toxin types was unclear. To examine the types of toxin, we designed primers for specific amplification of gene regions encoding the light chain (LC) domains for both BoNT/A and BoNT/B. After optimization, the expected PCR products were sent for sequencing. The results showed that the sequence of gene encoding BoNT/A LC was 99.2% identical to the CB-27 strain. The sequence of gene encoding BoNT/B LC was approximately 98.8% identical to reference strains. Additionally, we analyzed the sequences of the inferred proteins and identified a substitution that resulted in an early stop codon as previously found in a defective form of BoNT/B. Collectively, we provided the first evidence for C. botulinum strain possessing A(b) type in this studied outbreak. Further enzyme activity and neutralization assays are necessary to validate this preliminary toxin typing.